2013
DOI: 10.1016/s2095-3119(13)60346-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Application on Chlorophyll Fluorescence Parameters and Leaf Gas Exchange in Naked Oat

Abstract: Naked oat (Avena nuda L.) was originated from China, where there soil nitrogen (N) is low availability. The responses of chlorophyll (Chl) fluorescence parameters and leaf gas exchange to N application were analysed in this study. After the N application rate ranged from 60 to 120 kg hm-2 , variable fluorescence (Fv), maximal fluorescence (Fm), maximal photochemical efficiency (Fv/Fm), quantum yield (ΦPSII) of the photosynthetic system II (PSII), electron transport rate (ETR) and photochemical quenching coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 23 publications
5
30
0
1
Order By: Relevance
“…The Rd significantly 6 irradiance were able to maximize photosynthesis if CMR values were higher than 53 (about 2% of total N). The increase in maximum photosynthetic rate and light saturation point with higher CMR readings or N availability found in this study were also described by Lin et al (2013) in oats and by Xu et al (2014) in rice. The better relationship obtained between CMR readings and light-saturated photosynthesis with measurements on July 27th and August 17 th 2011 compared to the earlier instantaneous gas exchange measurements on June 23 rd and July 7 th can indicate that leaf photosynthesis became more limited by N availability later in the growing season.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The Rd significantly 6 irradiance were able to maximize photosynthesis if CMR values were higher than 53 (about 2% of total N). The increase in maximum photosynthetic rate and light saturation point with higher CMR readings or N availability found in this study were also described by Lin et al (2013) in oats and by Xu et al (2014) in rice. The better relationship obtained between CMR readings and light-saturated photosynthesis with measurements on July 27th and August 17 th 2011 compared to the earlier instantaneous gas exchange measurements on June 23 rd and July 7 th can indicate that leaf photosynthesis became more limited by N availability later in the growing season.…”
Section: Discussionsupporting
confidence: 82%
“…The R 2 of all fitted models were higher than 0.98. Nitrogen effects on gas exchange measurements in irrigated maize piration in N-deficient plants was also described by Gonzalez-Meler (1997) and Lin et al (2013) in wheat, pepper, and oats, respectively. However, the opposite effect was found in maize plants by Chen et al (2013), who reported lower Rd for plants grown in high-N supassimilation rates under N deficit.…”
Section: Discussionmentioning
confidence: 79%
“…In canopies of temperate forests, APAR has been found to explain 85% of the variance in SIF [14], but the evaluation of SIF can be very challenging for a complex canopy (such as tropical ones; [9]). Φ F is genotype-dependent and affected by shading [15] and by nitrogen availability [16]. The findings on the genotype dependency of vegetation fluorescence quantum yield in the band of 692 nm [15] suggest that floristic composition may define the Φ F of the forest.…”
Section: Introductionmentioning
confidence: 88%
“…Studying the light-response characteristics increases the understanding of photosynthesis (Lang et al 2011, Duan et al 2017. Chl fluorescence allows the rapid detection of plant photosynthesis and is commonly used to evaluate the functions of photosynthetic organs (Lin et al 2013). Studies on the relation between plant photosynthesis and N have shown that the application of N can increase Chl content and improve the activities of related enzymes to increase the photosynthetic capacity of leaves.…”
Section: Introductionmentioning
confidence: 99%